Meta Analisis Pengaruh Model Blended Learning terhadap Hasil Belajar IPS - Fauzatul Ma’rufah Rohmanurmeta (Graduate School of Universitas Negeri Malang, 2021)
Abstract: The purpose of this study was to reanalyze the existence of a blended learning model to improve social studies learning outcomes. The method used in this research is meta-analysis. This research activity includes problem formulation, tracing, and analyzing relevant research results. Data collection was carried out by searching electronic journals through Google Scholar with the keywords